Earth science and the environment - Thompson, Graham R (Thomson Brooks/Cole, 2007)
Using two themes, earth systems and environmental issues, EARTH SCIENCE AND THE ENVIRONMENT provides a rich overview of all Earth-related disciplines, including geology, meteorology, hydrology, oceanography, and astronomy. The authors provide a sense of how Earth functions as a single system composed of interacting subsystems and integrates coverage of enviromental issues in both the authoritative narrative and stunning multi-part visuals that emphasize the beauty of Earth science. To further enrich your experience, this earth science textbook is fully integrated with the CengageNOW online tutorial system. Web-based, assessment-driven, and completely flexible, the system provides you with a personalized learning plan based on a diagnostic pre-test to maximize your study time by focusing your attention where it is needed most.